Tensile strength of gabion wires against simulated weathering and field conditions - Tan, Kok-Keong; Chan, Chee-Ming; Liew, Allan (Penerbit Uthm, 2018)
Gabions can be applied in both civil and hydraulic engineering, it implies that gabions will be found in or on soil as retaining structures, along the streams and sea coast as erosion control structures. With such wide applications, the gabions must be built durable enough to withstand all possible site conditions that might weaken and damage the structure. However, the durability of the gabions relies greatly on the durability of the wire mesh as limited life of the wire basket is the major drawback of gabions [1]. To overcome, present coating technology which applies a polyvinyl chloride (PVC) or cross-linked polyethylene (XLPE) guaranteed the durability of gabions [2]